Genome‐wide association study of an unusual dolphin mortality event reveals candidate genes for susceptibility and resistance to cetacean morbillivirus. (26th December 2018) - Batley, Kimberley C.; Sandoval‐Castillo, Jonathan; Kemper, Catherine M.; Attard, Catherine R. M.; Zanardo, Nikki; Tomo, Ikuko; Beheregaray, Luciano B.; Möller, Luciana M.
Abstract: Infectious diseases are significant demographic and evolutionary drivers of populations, but studies about the genetic basis of disease resistance and susceptibility are scarce in wildlife populations. Cetacean morbillivirus (CeMV) is a highly contagious disease that is increasing in both geographic distribution and incidence, causing unusual mortality events (UME) and killing tens of thousands of individuals across multiple cetacean species worldwide since the late 1980s. The largest CeMV outbreak in the Southern Hemisphere reported to date occurred in Australia in 2013, where it was a major factor in a UME, killing mainly young Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ). Using cases (nonsurvivors) and controls (putative survivors) from the most affected population, we carried out a genome‐wide association study to identify candidate genes for resistance and susceptibility to CeMV. The genomic data set consisted of 278, 147, 988 sequence reads and 35, 493 high‐quality SNPs genotyped across 38 individuals. Association analyses found highly significant differences in allele and genotype frequencies among cases and controls at 65 SNPs, and Random Forests conservatively identified eight as candidates. Annotation of these SNPs identified five candidate genes ( MAPK8, FBXW11, INADL, ANK3 and ACOX3 ) with functions associated with stress, pain and immune responses. Our findings provide the first insights into the genetic basis of host defence to this highly contagious disease, enabling the development of an applied evolutionary framework to monitor CeMV resistance across cetacean species. Biomarkers could now be established to assess potential risk factors associated with these genes in other CeMV‐affected cetacean populations and species. These results could also possibly aid in the advancement of vaccines against morbilliviruses.